2008
DOI: 10.1152/ajpendo.00417.2007
|View full text |Cite
|
Sign up to set email alerts
|

Thermogenic effect of triiodothyroacetic acid at low doses in rat adipose tissue without adverse side effects in the thyroid axis

Abstract: Medina-Gomez G, Calvo RM, Obregon M-J. Thermogenic effect of triiodothyroacetic acid at low doses in rat adipose tissue without adverse side effects in the thyroid axis. Am J Physiol Endocrinol Metab 294: E688-E697, 2008. First published February 19, 2008 doi:10.1152/ajpendo.00417.2007.-Triiodothyroacetic acid (TRIAC) is a physiological product of triiodothyronine (T 3) metabolism, with high affinity for T 3 nuclear receptors. Its interest stems from its potential thermogenic effects. Thus this work aimed 1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 62 publications
1
36
0
Order By: Relevance
“…Intrahepatic TA 3 levels increase upon TA 3 infusion in rats, which is in line with the important role of the liver in TA 3 clearance (Medina-Gomez et al 2008). TA 3 also effectively induces the expression of T 3 -responsive genes in the liver, including Dio1, to a similar extent as T 3 (Juge-Aubry et al 1995, Liang et al 1997, Alvarez et al 2004, MedinaGomez et al 2008.…”
Section: Livermentioning
confidence: 71%
See 3 more Smart Citations
“…Intrahepatic TA 3 levels increase upon TA 3 infusion in rats, which is in line with the important role of the liver in TA 3 clearance (Medina-Gomez et al 2008). TA 3 also effectively induces the expression of T 3 -responsive genes in the liver, including Dio1, to a similar extent as T 3 (Juge-Aubry et al 1995, Liang et al 1997, Alvarez et al 2004, MedinaGomez et al 2008.…”
Section: Livermentioning
confidence: 71%
“…Interestingly, Mirell and coworkers (Mirell et al 1989) found that TSH mRNA expression levels are unchanged 6 h after TA 3 administration, suggesting that the initial decline in serum TSH is not caused by alterations at transcriptional level, but rather points to direct inhibition of TSH secretion by TA 3 . In contrast, prolonged (>12 days) TA 3 administration to rats persistently suppressed pituitary TSH mRNA levels (Juge-Aubry et al 1995, Liang et al 1997, resulting in a dose-dependent decrease in serum T 3 and T 4 levels (Medina-Gomez et al 2008). Similar effects on TSH levels were found in mice treated with TA 4 , whereas no effects were observed on hypothalamic TRH mRNA expression (Horn et al 2013).…”
Section: Effects Of Ta 3 On the Hypothalamuspituitary-thyroid (Hpt) Axismentioning
confidence: 71%
See 2 more Smart Citations
“…Triac concentrations may be up to 200 times the physiological concentration of T 3 . 7 On the other hand, high concentrations may cause various undesirable effects such as an increase of the heart rate and induction of arrhythmias, which might limit Triac's usefulness. 8 The solutions to these problems are among the main reasons for the development of new formulations such as polymeric nanoparticle systems.…”
Section: Introductionmentioning
confidence: 99%